Getting published in the life sciences - Gladon, Richard J.; Graves, William R.; Kelly, James Michael, 1944- (Hoboken, N.J. : Wiley-Blackwell, 2011)
'The goal of this book is to make it easier for scientists, especially those new to scientific writing, to write about their results and to get their manuscripts accepted in peer-reviewed journals. The book covers each step throughout the submission process, from organizing and outlining the manuscript, presenting statistical data and results, to what happens during the in-house manuscript review process and what to do if an article is initially rejected. In addition to providing practical exercises on these topics, the book focuses on helping writers distil their research into concise take-home messages for readers, in order to convey information as clearly as possible to the target audience'--
'The goal of this book is to make it easier for scientists, especially those new to scientific writing, to write about their results and to get their manuscripts accepted in peer-reviewed journals. The book covers each step throughout the submission process, from organizing and outlining the manuscript, presenting statistical data and results, to what happens during the in-house manuscript review process and what to do if an article is initially rejected'--
Includes bibliographical references and index.
Keywords: Biology -- Authorship; Authorship -- Marketing; Technical writing -- Vocational guidance